ANALISIS FUNGSI TEKSTUAL DALAM SURAT KABAR HARIAN â€œHALUANâ€ - Rosa, Rusdi Noor (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2007)
This study is aimed at applying Halidayâ€™s theory of textual function in writing editorials of â€œHaluanâ€ daily newspaper. The theory says that unmarked theme tends to be used if a newspaperâ€™s editorial shows an agreement with certain issues widely spread throughout the community. Meanwhile, marked theme is mostly used when a newspaperâ€™s editorial shows disagreement with certain issues. This study takes 10 editorial texts of â€œHaluanâ€ daily newspaper as the source of data. These editorials were published from May to July 2006. Based on the findings, 8 out of 10 editorials use marked theme as the most dominant theme type, while the other two editorials use unmarked theme most frequently. These findings show that both theme types are used in Haluanâ€™s editorials. It is also found that Halidayâ€™s theory is applied in writing editorials of â€œHaluanâ€: unmarked theme shows an agreement, while marked theme indicates a disagreement. Nevertheless, in some editorials, Halidayâ€™s theory is not applied.